MORAL VALUE IN THE NOVEL MANUK PRENJAK MABUR ING PENGGING BY ENDANG WIRYANTI AND THEIR RELEVANCE IN EVERYDAY LIFE - Dewi Saputri, Riska; Setyowati, Herlina; Widiyono, Yuli (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2024)
The purpose of this study is to describe the moral values in the novel Manuk Prenjak Mabur ing Pengging by Endang Wiryanti and its relevance in everyday life. Suminto A. Sayuti's story facts and Burhan Nurgiyantoro's moral values are used in the research analysis. This research is descriptive qualitative. The research data is in the form of quotations and dialog in the novel which includes moral values and their relevance. Data collection methods include library, listening, and note-taking techniques, while data analysis is done through reduction, presentation, and conclusion drawing. The results of the analysis show that moral values in the novel include human relationships with God, fellow humans, the social environment, nature, and oneself. These values are influential in daily life, forming the basis of ethics and good behavior, as well as helping to create balance in interactions, strengthen social ties, preserve the environment, and develop a responsible and highly moral person. Thus, these moral values play an important role in creating a more harmonious, meaningful life.